2013
DOI: 10.1021/ol4006618
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoramidite–Cu(OTf)2 Complexes as Chiral Catalysts for 1,3-Dipolar Cycloaddition of Iminoesters and Nitroalkenes

Abstract: Chiral complexes formed by phosphoramidites such as (S a ,R,R)-9 and Cu(OTf) 2 are excellent catalysts for the general 1,3-dipolar cycloaddition between azomethine ylides and nitroalkenes affording the corresponding tetrasubstituted proline esters mainly as exo-cycloadducts in high er at room temperature. The exo-cycloadducts can be obtained in enantiomerically pure form just after simple recrystallization. DFT calculations support the stereochemical results.Substituted prolinates 1, obtained from the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 26 publications
4
36
0
1
Order By: Relevance
“…The isolation of equimolecular quantities of exocycloadduct 5 and non-characterized syn-imine 41 followed by acidic work up allowed to obtain -amino ester 42 in 40% yield, 98:2 dr, and 94% ee (Scheme 14). In addition, DFT calculations and parallel theoretical studies confirmed the low energy barrier for the previous transition state to the generation of this major exo-isomer 5 [59]. The mechanism of these metal catalyzed 1,3-DC can be exemplified by DFT calculations on the 30·Cu(OTf) 2 catalyzed reaction to obtain exo-5 (R 1 = Ph, R 3 = Ph, R 4 = H, R 5 = Me).…”
Section: Chiral Copper Complexes As Catalystsmentioning
confidence: 64%
See 1 more Smart Citation
“…The isolation of equimolecular quantities of exocycloadduct 5 and non-characterized syn-imine 41 followed by acidic work up allowed to obtain -amino ester 42 in 40% yield, 98:2 dr, and 94% ee (Scheme 14). In addition, DFT calculations and parallel theoretical studies confirmed the low energy barrier for the previous transition state to the generation of this major exo-isomer 5 [59]. The mechanism of these metal catalyzed 1,3-DC can be exemplified by DFT calculations on the 30·Cu(OTf) 2 catalyzed reaction to obtain exo-5 (R 1 = Ph, R 3 = Ph, R 4 = H, R 5 = Me).…”
Section: Chiral Copper Complexes As Catalystsmentioning
confidence: 64%
“…Thus, exo-TS1 was found to be about 1.5 kcal mol -1 more stable than its enantiomeric counterpart. New carbon-carbon bond distances were very different to each other demonstrating the already mentioned asynchronous cyclization [59].…”
Section: Chiral Copper Complexes As Catalystsmentioning
confidence: 75%
“…Again, the p-substitution resulted to be most favorable for this transformation such as it was exemplified in Table 10 and Scheme 22. Higher diastereoselections were achieved in these examples together with excellent enantioselectivities [94]. 2 catalyzed reaction to obtain 53 (R 1 = Ph, R 2 = H, R 3 = Me, R 4 = Ph), showed that the coordination sphere of copper(II) atom is saturated by a OTf moiety.…”
Section: Scheme 22mentioning
confidence: 85%
“…The 2-naphthyl derivative gave a 86/14 exo:endo diasteromeric ratio with a good er of product 53. The p-substitution increased these two parameters up to 93/7 exo/endo ratio with higher enantioselections (up to >99 ee after recrystallization) [94]. The insertion of an α-substituent in the dipole precursor afforded different behavior depending on the alkyl substituent.…”
Section: Scheme 22mentioning
confidence: 96%
See 1 more Smart Citation